Survival Trends After Surgery for Spinal Metastatic Tumors: 20-Year Cancer Center Experience. Issue 2 (24th September 2020) - Rothrock, Robert J; Barzilai, Ori; Reiner, Anne S; Lis, Eric; Schmitt, Adam M; Higginson, Daniel S; Yamada, Yoshiya; Bilsky, Mark H; Laufer, Ilya
Abstract: BACKGROUND: Over the last 2 decades, advances in systemic therapy have increased the expected overall survival for patients with cancer. It is unclear whether the same survival benefit has been conferred to patients requiring surgery for metastatic spinal disease. OBJECTIVE: To examine trends in postoperative survival over a 20-yr period for patients surgically treated for spinal metastatic disease. METHODS: Data were obtained for 1515 patients who underwent surgery for metastatic epidural spinal cord compression or tumor-related mechanical instability. Postoperative overall survival was calculated for all included patients using Kaplan-Meier methodology from date of surgery until death or last follow-up for those who were censored. Trends were analyzed using Cox proportional hazards modeling. RESULTS: Patients with renal, breast, lung, and colon cancers experienced a statistically significant improvement in survival over time based on the year of surgery (40%-100% improvement over the study period), whereas the overall survival trend for the entire cohort did not reach statistical significance ( P  = .12, median survival 0.71 yr, 95% CI 0.63-0.78). Patients presenting with synchronous metastatic disease had better survival compared to those presenting with metachronous disease (median overall survival: 0.94 vs 0.63 yr, respectively; log-rank P -value = .00001). CONCLUSION: The postoperative survival among patients with spinal metastases has improved over the past 20 yr, particularly in patients with kidney, breast, lung, and colon tumors metastatic to the spine. The observed survival improvement emphasizes the need for long-term outcome consideration in treatment decisions for patients undergoing surgery for spinal metastatic tumors.